Prevalence of Cysticercus Tenuicollis and associated risk factors of small ruminants slaughtered at Jimma Municipal Abattoir, South West Ethiopia - Yitegasu Seyoum Gulilat; Nemomsa Anbese Jiru , (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
This study was conducted from April 2018 to May 2018 in Jimma municipal abattoir, south west of Ethiopia. The aims of this study were to determine the prevalence of C. Tenuicollis in sheep and goat slaughtered at Jimma municipal abattoir and to identify risk factors that can influence the prevalence of C.Tenuicollis. Ante-mortem and post-mortem inspection were conducted. Ante-mortem inspection was conducted in the lairage and abnormalities encountered were recorded, followed by postmortem examination through their identification number to detect gross abnormalities. During the study, a total 109 goats and 275 sheep visceral organs were inspected. C. Tenuicollis was found in 14 goats (12.84%) and 46 sheep (16.72%), respectively. C.Tenuicollis had a tendency to be located more in the mesentery than other organs and this difference between infections rate of mesentery and other organs was not significantly associated (p>0.05). This study also shows that C. Tenuicollis is more frequently detected in the mesentery of goats and sheep than any other visceral organs. Appropriate control measures need to be introduced to reduce the prevalence of these parasites in small ruminants. So as to reduce these losses, further studies should be done in different abattoirs of the country and introduce preventive measures to reduce unnecessary financial losses.